Sulphate-resistant barium-containing portland cement for cementing oil and gas wells - Zolotarov, Kyrylo (National Technical University "Kharkiv Polytechnic Institute", 2025)
The recent decline in gas production in Ukraine is largely attributed not to the depletion of its resource base, but to the overexploitation of easily recoverable reserves and the lack of development of more complex ones. As a result, the search for new hydrocarbon reserves and the redevelopment of existing fields are becoming increasingly challenging. These efforts are further complicated by the need to operate under extreme well conditions, including high pressure and temperature (HPT), which are becoming more common in modern oil and gas exploration and production.
Keywords: Ukraine; gas production; hydrocarbon reserves; HPT conditions; reservoir pressure; reservoir temperature; resource depletion